Fusing Machine Learning and AI to Create a Framework for Employee Well-Being in the Era of Industry 5.0 - Cosmina-Mihaela Rosca; Adrian Stancu (Applied Sciences)
Employees are the most valuable resources in any company, and their well-being directly influences work productivity. This research investigates integrating health parameters and sentiment analysis expressed in sent messages to enhance employee well-being within organizations in the context of Industry 5.0. Our primary aim is to develop a Well-Being Index (WBI) that quantifies employee health through various physiological and psychological parameters. A new methodology combining data collection from wearable devices from 1 January 2023 to 18 October 2024 and advanced text analytics was employed to achieve the WBI. This study uses the LbfgsMaximumEntropy ML classification algorithm to construct the Well-Being Model (WBM) and Azure Text Analytics for sentiment evaluation to assess negative messages among employees. The findings reveal a correlation between physiological metrics and self-reported well-being, highlighting the utility of the WBI in identifying areas of concern within employee behavior. We propose that the employee global indicator (EGI) is calculated based on the WBI and the dissatisfaction score component (DSC) to measure the overall state of mind of employees. The WBM exhibited a MacroAccuracy of 91.81% and a MicroAccuracy of 95.95% after 384 configurations were analyzed. Azure Text Analytics evaluated 2000 text messages, resulting in a Precision of 99.59% and an Accuracy of 99.7%. In this case, the Recall was 99.89% and F1-score was 99.73%. In the Industry 5.0 environment, which focuses on the employee, a new protocol, the Employee KPI Algorithm (EKA), is integrated to prevent and identify employee stress. This study underscores the synergy between quantitative health metrics and qualitative sentiment analysis, offering organizations a framework to address employee needs proactively.